2020
DOI: 10.1080/15548627.2020.1831814
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Env induces pexophagy and an oxidative stress leading to uninfected CD4+ T cell death

Abstract: The immunodeficiency observed in HIV-1-infected patients is mainly due to uninfected bystander CD4 + T lymphocyte cell death. The viral envelope glycoproteins (Env), expressed at the surface of infected cells, play a key role in this process. Env triggers macroautophagy/autophagy, a process necessary for subsequent apoptosis, and the production of reactive oxygen species (ROS) in bystander CD4 + T cells. Here, we demonstrate that Env-induced oxidative stress is responsible for their death by apoptosis. Moreove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…The HIV life cycle could end with cell death of infected cells or by HIV-1 Env-mediated cell death of uninfected bystander cells (Mohammadi et al, 2013;Cummins and Badley, 2014;Doitsh and Greene, 2016;Li et al, 2020) which occurs during early infection (Espert et al, 2008(Espert et al, , 2009. Hence, one of the most relevant HIV-1 modulators of cell death is the Env glycoprotein (Krüger et al, 1996;Blanco et al, 2001;Vlahakis et al, 2001;Blumenthal, 2006, 2008;Varbanov et al, 2006;Garg et al, 2009;Sivaraman et al, 2009;Gorry and Ancuta, 2011;Cicala et al, 2016;Joshi et al, 2016;Tsao et al, 2016;Evering, 2018;Daussy et al, 2020).…”
Section: The Role Of Autophagy In the Early Steps Of Hiv-1 Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The HIV life cycle could end with cell death of infected cells or by HIV-1 Env-mediated cell death of uninfected bystander cells (Mohammadi et al, 2013;Cummins and Badley, 2014;Doitsh and Greene, 2016;Li et al, 2020) which occurs during early infection (Espert et al, 2008(Espert et al, , 2009. Hence, one of the most relevant HIV-1 modulators of cell death is the Env glycoprotein (Krüger et al, 1996;Blanco et al, 2001;Vlahakis et al, 2001;Blumenthal, 2006, 2008;Varbanov et al, 2006;Garg et al, 2009;Sivaraman et al, 2009;Gorry and Ancuta, 2011;Cicala et al, 2016;Joshi et al, 2016;Tsao et al, 2016;Evering, 2018;Daussy et al, 2020).…”
Section: The Role Of Autophagy In the Early Steps Of Hiv-1 Infectionmentioning
confidence: 99%
“…Furthermore, after contact between CD4 + T lymphocytes and Env-expressing cells, reactive oxygen species (ROS) are accumulated and its production is known to be involved in autophagy (Molina et al, 2007;Borel et al, 2012). It has recently been reported that peroxisomes, organelles involved in the control of oxidative stress, are targeted by Env-mediated autophagy, inducing oxidative stress and this leads to uninfected CD4 + T cells death (Daussy et al, 2020).…”
Section: Hiv-1 Env-mediated Regulation Of Autophagy and Related Factors During Early Infection In T Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…This interconnection might be relevant, as we recently showed that HIV-1 infection leads to enhancement of antioxidant defenses in primary CD4 + T-cells (Shytaj et al, 2020). HIV-1 infection causes an initial oxidative stress (Daussy et al, 2020), which then leads to the nuclear translocation of the master antioxidant transcription factor Nrf2. This translocation in turn induces transcription of several proteins involved in antioxidant response, including glucose 6-phosphate dehydrogenase (G6PDH), which diverts glucose 6-phosphate from the glycolytic pathway to the pentose cycle, responsible for production of the antioxidant NADPH.…”
Section: Introductionmentioning
confidence: 94%
“…A study showed that expression of HIV viral envelope glycoproteins (Env) triggers massive macroautophagy/autophagy as well as pexophagy, which results in the elimination of mature peroxisomes in CD4 + T cells. In addition, Env expression induces a dramatic increase in cellular ROS, which induces cell death [ 80 ]. The study suggested that reducing the number of functional peroxisome through pexophagy may enhance oxidative stress, which can damage CD4 + T cells and contribute to the acquired immunodeficiency observed in HIV-1-infected patients.…”
Section: Roles Of Pexophagy In Health and Diseasementioning
confidence: 99%